A Study of Factors Related to Retired Consumers’ Purchase Decisions on TikTok Shop Using Digital Data Visualization Tools - ปาสาบุตร, อนุภัทร; ปานพิตร, อาทิตย์; อรุณกุลประภา, ธานัท; รักแหยม, ปฐมพร; นาคสุข, พุทธินันท์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this study were to 1) examine the behavior of retired consumers in using TikTok and purchasing products through TikTok Shop, 2) analyze the factors related to retired consumers’ purchase decisions on TikTok Shop, and 3) present the analytical results of these factors. This research employed a quantitative research approach. The sample consisted of 236 retired consumers who had previously made online purchases, selected using purposive sampling based on criteria aligned with the research objectives. The research instruments included an online questionnaire for data collection, and the data were analyzed using statistical methods.            The findings revealed that the majority of respondents were female (68.2%), aged between 55-60 years (38.1%), with an average monthly income of 10,001-20,000 baht (54.7%). Most respondents used TikTok 2-3 times per week (39.0%), while their purchasing frequency was occasional (51.3%). The most popular product category was health and beauty products (71.6%). The factor most strongly related to purchase decisions was confidence in payment and delivery systems (= 4.06, S.D. = 0.88). In addition, retired consumers exhibited highly positive attitudes toward using TikTok Shop and reported a high level of satisfaction with their purchasing experience (= 4.00). The results indicate that system reliability and user experience are key factors associated with purchase decisions among retired consumers, which can be applied to develop effective marketing strategies for digital platforms.